Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1074/jbc.m114.614297
|View full text |Cite
|
Sign up to set email alerts
|

Sites Involved in Intra- and Interdomain Allostery Associated with the Activation of Factor VIIa Pinpointed by Hydrogen-Deuterium Exchange and Electron Transfer Dissociation Mass Spectrometry

Abstract: Background: Site-specific hydrogen-deuterium exchange of factor VIIa (FVIIa) was measured to elucidate the mechanism by which FVIIa is up-regulated by tissue factor (TF). Results: Individual residues in FVIIa whose interaction pattern changes when TF induces the active form are pinpointed. Conclusion: A picture of the activation signal from TF contact site to active site emerges. Significance: Guidance for future work on FVIIa allostery is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…At the completion of this study, we conclude that whole‐protein alanine‐scanning mutagenesis is a useful tool to identify protein residues that potentially contribute to allosteric mechanisms. In particular, this probing approach is likely to be complementary to the protein backbone monitoring offered by hydrogen/deuterium exchange (Beckett, ; Frantom, Zhang, Emmett, Marshall, & Blanchard, ; Landgraf et al., ; Prasannan et al., ; Song, Olsen, Persson, & Rand, ; Underbakke et al., ). This independent method will also be beneficial to guide structural comparisons to focus on which regions of a protein might experience allosterically relevant conformational and/or dynamic changes.…”
Section: Discussionmentioning
confidence: 99%
“…At the completion of this study, we conclude that whole‐protein alanine‐scanning mutagenesis is a useful tool to identify protein residues that potentially contribute to allosteric mechanisms. In particular, this probing approach is likely to be complementary to the protein backbone monitoring offered by hydrogen/deuterium exchange (Beckett, ; Frantom, Zhang, Emmett, Marshall, & Blanchard, ; Landgraf et al., ; Prasannan et al., ; Song, Olsen, Persson, & Rand, ; Underbakke et al., ). This independent method will also be beneficial to guide structural comparisons to focus on which regions of a protein might experience allosterically relevant conformational and/or dynamic changes.…”
Section: Discussionmentioning
confidence: 99%
“…This effect became even more pronounced in the presence of sTF with the cofactor still able to mature the S1 pocket to FVIIa-WT levels through the proposed pathway II (10) but unable to potentiate amidolytic activity. The unfavorable conformation of the TF-binding helix may explain this as it is likely to result in the low extent of N terminus insertion, which without the effects of Tyr 172 results in a signif- icant destabilization of the whole activation pocket and the active site (5 (20) where an increase in Trp 215 backbone amide protection was seen upon sTF addition. The combined approach of SASA calculation and in-solution quenching used here allowed an elaboration on these observations.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of FVIIa-Y T in complex with sTF revealed that Tyr 172 , as in trypsin (45) (20). In addition, the hydroxyl group of Tyr 172 displaces a water molecule (HOH 1 ; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 Reduced N-terminal hydrogen-deuterium exchange upon TF binding to FVIIa supports the hypothesis that the N-terminal Ile 153 is not fully inserted into the activation pocket when free in solution. 51 Additionally, unlike most other serine proteases, oxyanion hole formation in free FVIIa does not occur upon proteolytic activation, but instead upon substrate interaction. 52 As a result, FVIIa circulates in a zymogen-like state that is poorly recognized by plasma protease inhibitors, 52 allowing it to circulate with a half-life of 90 minutes.…”
Section: Structure Tissue Factormentioning
confidence: 99%